Asymmetric synthesis of gem-difluoromethylenated dihydroxypyrrolizidines and indolizidines - Watcharaporn Thaharn (2018)
An asymmetric synthesis of gem-difluoromethylenated dihydroxypyrrolizidines and indolizidines is described. The fluoride-catalyzed nucleophilic addition of PhSCF 2 SiMe 3 (1) to chiral imides was achieved in satisfactory yields to provide mixtures of syn- and anti-isomers 6-9 with moderate to good diastereoselectivities. Reductive cleavage of the phenylsulfanyl group followed by intramolecular radical cyclization of the syn-isomers 6-9 occurred under refluxing conditions to afford the corresponding gem-difluoromethylenated 1-azabicyclic compounds 10-13 in moderate yields as a separable mixture of cis- and trans-isomers. The cis-isomers of compounds 10 and 12 and trans-13 were readily transformed to gem-difluoromethylenated dihydroxypyrrolizidines 20 and 27 and indolizidine 28, respectively, by reductive cleavage of the hydroxyl group and organometallic addition followed by hydrogenolysis. © 2012 American Chemical Society.